LAPAROSCOPIC RESECTION OF GASTROINTESTINAL STROMAL TUMORS (GIST) - Loureiro,Marcelo de Paula (2016)
Background : Gastrointestinal mesenchymal or stromal tumors (GIST) are lesions originated on digestive tract walls, which are treated by surgical resection. Several laparoscopic techniques, from gastrectomies to segmental resections, have been used successfully. Aim : Describe a single center experience on laparoscopic GIST resection. Method : Charts of 15 operated patients were retrospectively reviewed. Thirteen had gastric lesions, of which ten were sub epithelial, ranging from 2-8 cm; and three were pure exofitic growing lesions. The remaining two patients had small bowel lesions. Surgical laparoscopic treatment consisted of two distal gastrectomies, 11 wedge gastric resections and two segmental enterectomies. Mechanical suture was used in the majority of patients except on six, which underwent resection and closure using manual absorbable sutures. There were no conversions to open technique. Results : Mean operative time was 1h 29 min±92 (40-420 min). Average lenght of hospital stay was three days (2-6 days). There were no leaks, postoperative bleeding or need for reintervention. Mean postoperative follow-up was 38±17 months (6-60 months). Three patients underwent adjuvant Imatinib treatment, one for recurrence five months postoperatively and two for tumors with moderate risk for recurrence . Conclusion : Laparoscopic GIST resection, not only for small lesions but also for tumors above 5 cm, is safe and acceptable technique.